Development of a Website-Based Industrial Practice Management System - Alifya NFH; Ayu Tri Wardani (Fakultas Teknik Universitas Negeri Makassar, 2026)
This research aims to develop an integrated website-based Industrial Practice Management System (PI) to digitize the entire PI process, improve administrative efficiency, and support monitoring and evaluation of student activities. This research uses the Research and Development method with the Waterfall software development model. The development stages include needs analysis, system design, implementation, system integration and testing with the black box method. The system developed has features of assessment, provision, PI registration, daily logbook management, seminar submission, approval process, and the appointment of supervisors in one platform. Functional testing was conducted against 90 test scenarios covering 19 functional needs. The test results show that all scenarios obtain a status of